Information users as the goal of university libraries: an analysis based on Adorno and Horkheimer's Critical Theory - Gomes de Mello, Mariana Rodrigues [UNESP]; Camillo, Everton Da Silva [UNESP]; Gardini Santos, Joao Carlos [UNESP]; Martinez-Avila, Daniel (Univ Federal Rio Grande Sul, Fac Biblioteconomia & Comunicacao, 2021)
This paper aims to investigate whether the emancipatory reason in the Frankfurt School's critical theory is aligned with the expectations of the users of information services and resources in universities of the Southeast region of Brazil offering graduate programs in Information Science. The research hypothesis is that information users in these Programs constitute the main goal of the information services and resources of these university libraries. The study presents the relationship between critical theory in Theodor Adorno and Max Horkheimer with the approaches of the information user studies. It discusses the traditional and alternative approaches on user studies and their relationship with the function of university libraries. The survey data were collected through the application of a questionnaire. The Content Analysis research method was applied by establishing five topics and fifteen categories. The research findings reveal that the topics 'Access/organization of the library and the collection' and 'Collaborators' were aligned with the emancipatory reason. The topics 'Products' and 'Services' correspond both to the categories aligned with the instrumental reason. Thus, the hypothesis was refuted. The paper concludes that information services and resources are essential for information users to become emancipated. However, for university libraries to be able to act socially according to the emancipatory reason, it is required approaching the information users as the very end of university libraries' actions and not just as the mean of them.
Keywords: University library; User studies; Information users; Critical theory